1998
DOI: 10.1021/ac970805y
|View full text |Cite
|
Sign up to set email alerts
|

Regenerable Biosensor Platform:  A Total Internal Reflection Fluorescence Cell with Electrochemical Control

Abstract: A new biosensor platform that provides simultaneous fluorescence detection and electrochemical control of biospecific binding has been developed and investigated using antibody-antigen and streptavidin-biotin interactions. Specifically, biotin was covalently bound to a transparent indium-tin oxide (ITO) working electrode, which also served as an integral part of a total internal reflection fluorescence (TIRF) flow cell. TIRF was used to monitor biospecific interactions, while electrochemical polarization was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
116
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(116 citation statements)
references
References 12 publications
0
116
0
Order By: Relevance
“…The influence of an applied electric potential on the adsorption of charged macromolecules (mainly proteins) has been the subject of several previous investigations (19,20,(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44). Although most of these studies note an influence of substrate potential on adsorption, changes are typically within a factor of two or so, and to our knowledge no continuous adsorption has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of an applied electric potential on the adsorption of charged macromolecules (mainly proteins) has been the subject of several previous investigations (19,20,(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44). Although most of these studies note an influence of substrate potential on adsorption, changes are typically within a factor of two or so, and to our knowledge no continuous adsorption has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…However, improvements are required in many areas, such as prevention of non-specific binding [302][303][304][305][306], sensitivity [307][308][309][310][311][312][313][314][315], site-specific conjugation [316][317][318], bioactivity [319][320][321][322], multiplexing [309,323], and reusability [324][325][326]. Some of these problems can be addressed by using different chemical surface modification approaches.…”
Section: Biosensing-detectionmentioning
confidence: 99%
“…It was found that a fabricated immunosensor based on MHDA-SAM could retain its activity for at least 1 week at 4 °C before its first use. How to regenerate a sensor for continuous use is a challenge for the majority of immunosensors, because the regeneration with extreme pH, temperature and chaotropic agents would decrease the activity significantly (Asanov et al, 1998). There were many methods proposed to settle on the solution to this problem, whose goal was to effectively dissociate most antibody-antigen binding interactions without permanently affecting protein structure, so the regenerated immunosensor could be used to detect the target bacteria again.…”
Section: Stability and Repeatability Of Immunosensormentioning
confidence: 99%